Tujuan Pembangunan Berkelanjutan (SDGs) dan Konsep Pembangunan Masyarakat di Negara-negara Kepulauan Kecil: Madagaskar dan Maladewa - Syakirin, Jamaluddin; Susanto, Siti Rokhmawati (Kajian Hubungan Internasional, 2025)
The implementation of the Sustainable Development Goals (SDGs) serves as a development benchmark in various countries to achieve balanced and sustainable global development. This presents various challenges, depending on the capabilities of each country. Small island nations, in addition to unique circumstances, also face program adaptations to achieve the SDGs, as determined by the target milestones. Community development programs in Madagascar and the Maldives demonstrate similarities and different approaches, tailored to the unique contexts of each country. This article employs a comparative case study methodology, analyzing secondary data from government reports, NGO initiatives, and academic literature on SDG-related programs in both nations. Key findings reveal that while both countries prioritize poverty alleviation through livelihood diversification (e.g., fisheries in the Maldives and agriculture in Madagascar), environmental sustainability efforts differ: the Maldives focuses on climate-resilient tourism, whereas Madagascar emphasizes reforestation and biodiversity conservation. These approaches enhance community quality of life but highlight resource constraints in small islands. The study concludes that context-specific adaptations are essential for SDG success, offering policy recommendations for other vulnerable nations.